Case Report: Use of veterinary cuttable plates to maintain reduction and reinforce polymethylmethacrylate (PMMA) fixation in two canine C2 vertebral fractures - Snead, Olivia M.; Law, Andy Y.; MacRae, Megan R.; Yoder, Hannah R.; Kraus, Karl H. (Frontiers in Veterinary Science, 2025)
Veterinary cuttable plates (VCPs) were used to maintain reduction and provide reinforcement in screw and polymethylmethacrylate (PMMA) repairs of C2 vertebral fractures in two dogs. A 6-month-old male intact 3.8 kg Shih Tzu and a 4-year-old male intact 30.5 kg Golden Retriever presented after motor vehicle accidents. Computed tomography (CT) scans revealed fractures of the C2 vertebrae in both dogs. Fractures were reduced and stabilized with a combination of cortical screws, VCPs, and PMMA. The novel technique utilized veterinary cuttable plates positioned between screws cranial and caudal to the fracture for distraction and reduction of the fractures and can be incorporated into the acrylic. Post-operative imaging showed adequate fracture reduction and relief of spinal cord compression. Recheck examinations demonstrated a return to normal and near-normal neurologic function in both patients.